A Large Linked Study to Evaluate the Future Burden of Cancer in Australia Attributable to Current Modifiable Behaviours. (2018) - Laaksonen, Maarit A; Arriaga, Maria E; Canfell, Karen; MacInnis, Robert; Hull, Peter; Banks, Emily; Giles, Graham G; Mitchell, Paul; Cumming, Robert G; Byles, Julie E; Magliano, Dianna J; Shaw, Jonathan; et al.
No abstract available